Analysis of Physics Education Students’ Ability to Design Physics Education Research Proposals - Sri Handayani Parinduri (Institut Agama Islam Negeri Padangsidimpuan, 2026)
The ability to design research proposals is an important academic competency for Physics Education students because it reflects their ability to transform learning problems into scientific research designs. This study aims to analyze the ability of sixth-semester students in the Physics Education Program to design physics education research proposals for the 2025/2026 academic year. The study employed a descriptive qualitative approach with four students selected through purposive sampling as participants. Data were collected through the analysis of draft proposal documents, semi-structured interviews, and observations of the academic consultation process. Data analysis utilized the interactive model by Miles, Huberman, and Saldana, which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that the students’ abilities generally fall into the “adequate” category. Students were relatively capable of determining themes and titles relevant to physics learning but still experienced difficulties in identifying research gaps, formulating novelty, synthesizing theory, selecting research designs, developing instruments, and determining data analysis techniques. These findings underscore the need to strengthen the research methodology course through mini-research projects, journal reviews, proposal clinics, and guidance on instrument development.